E-LEARNING AND ONLINE EDUCATION IN THE DIGITAL ERA (American Journal of Interdisciplinary Research and Development, 2026)
The rapid digitalization of modern society has significantly transformed the structure and philosophy of education. Over the last decade, e-learning and online education have shifted from being supplementary instructional tools to becoming strategic pillars of global educational systems. This research explores the evolution, pedagogical foundations, advantages, challenges, and long-term implications of digital learning in the contemporary era.